2006
DOI: 10.1111/j.1440-1746.2006.04227.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of cirrhotic patients undergoing cholecystectomy: Applying Bayesian analysis in gastroenterology

Abstract: Laparoscopic cholecystectomy is a safe and effective alternative to OC in Child-Pugh class A and B cirrhotic patients undergoing elective or emergent cholecystectomy. Although outcomes of cirrhotic patients undergoing LC and OC in a tertiary center are not different, LC is associated with less intraoperative bleeding, shorter duration of surgery and fewer days of in-hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A large body of research has demonstrated that LC in patients with early, well-compensated cirrhosis is safe and offers advantages over the open approach [57]. However, the cirrhotic background and severe inflammation may prolong the operative time and increase both blood loss and the conversion rate to an open procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research has demonstrated that LC in patients with early, well-compensated cirrhosis is safe and offers advantages over the open approach [57]. However, the cirrhotic background and severe inflammation may prolong the operative time and increase both blood loss and the conversion rate to an open procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The 1992 National Institutes of Health consensus stated that end‐stage liver cirrhosis is a contraindication to laparoscopic cholecystectomy (LC) 4 . In the last 10 years there has been a growing body of evidence that laparoscopic cholecystectomy in patients with early, well‐compensated cirrhosis is safe and has advantages over the open approach 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…A case control study showed the conversion and morbidity rate was higher in the cirrhosis group than in the control group (Fernandes, 2000), (Treatment studies 3b); and two case series shows similar results than the previous RCT reported in patients with cirrhosis and portal hypertension Child A and B (Palanivelu, 2006;da Silveira, 2006).…”
Section: (Treatment Studies 2b)mentioning
confidence: 44%
“…Low quality: it very likely that future studies change our confidence in the estimate of effect, therefore our confidence is low. Table. 2001; Elder, 1996;Finan, 2006;Zacks, 2002;Collet, 1997;Ibrahim, 2006;Weber, 2003;Feldman, 1994;Perez Lara, 2006;Sungler, 2000;Daradkeh, 1999;Ji, 2005;Fernandes, 2000;Palanivelu, 2006;da Silveira, 2006;Gurusamy, 2006;Chandler, 2000;Kiviluoto, 1998;Glavic, 2001;Eldar, 1998;Lujan, 1995;Tan, 2006;Perez-Morales, 2005;Bagia, 2001;Schafer, 2003;Kwon, 2001;Woods, 1996).…”
Section: Discussionmentioning
confidence: 99%